If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + xy = 0 Solving 2x + xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'x'. x(2 + y) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(2 + y)' equal to zero and attempt to solve: Simplifying 2 + y = 0 Solving 2 + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + y = 0 + -2 y = 0 + -2 Combine like terms: 0 + -2 = -2 y = -2 Add '-1y' to each side of the equation. y + -1y = -2 + -1y Combine like terms: y + -1y = 0 0 = -2 + -1y Simplifying 0 = -2 + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| -144=-70+X | | (3x+12)/(x+4) | | x=700/5 | | -5(3b+2)+(16b-6)=0 | | 6n^2-3n= | | 0.8x-1=4.1 | | 15n=-9 | | x=100/7x5 | | N-(-100)=165 | | a^2+3a-28=0 | | -19.29+2y=2.74+3y | | 1000=x+3(x+50) | | w(w-2)=0 | | q=1.7+3.2-0.4 | | 4(3+7)= | | 0=-16t^2+42t-20 | | f(x)=(x+3)(2x-1)(x+2) | | 2(3y)-y=5 | | 1-10x=-29 | | X+(-12)=-5 | | (4.5*0.5)/s=7.5 | | 4.5*0.5= | | 57=2a+(a-3)+a | | 0.12(m-5)=0.96 | | 25y^2=81 | | 6x-4(2/7x+2)=-21 | | 4.3q-1.3-5.3q=-2.0q-2.3 | | 3x+6=3x*6 | | 3x+9=2x+6 | | -4(3+4)-21x=72 | | 9-4(2p-1)=46 | | 2a+3a+a=57 |